Effects of ABO Blood Groups and Helicobacter pylori on COVID-19 Susceptibility and Disease Severity: Findings from a Cross-Sectional Analysis - Maryam Nejabat; Mohammad Motamedifar; Saeid Amiri Zadeh Fard (Iranian Journal of Colorectal Research)
Background: The investigation of the correlation between ABO blood groups and susceptibility to infectiousdiseases, particularly COVID-19 and Helicobacter pylori (H. pylori), has garnered significant scholarlyattention in recent studies. This study aimed to evaluate the association between ABO blood groups and H.pylori infection with COVID-19 susceptibility and severity.Methods: This cross-sectional study was conducted from October 1, 2021 to March 31, 2023. During thisperiod, serum samples from 1,105 patients diagnosed with COVID-19 at hospitals affiliated with ShirazUniversity of Medical Sciences were analyzed for SARS-CoV-2 and H. pylori antibodies using the enzymelinkedimmunosorbent assay (ELISA) technique. Clinical data, including demographic characteristics andmanifestations of COVID-19, were collected through structured interviews and comprehensive reviews ofmedical records.Results: The prevalence of COVID-19 was significantly higher among individuals with blood group Acompared to other groups (P=0.032). Patients co-infected with H. pylori had more severe COVID-19 symptoms(P=0.021). The findings from this investigation reveal that blood group O is correlated with an increased riskfor both COVID-19 and H. pylori infections, whereas blood group AB demonstrates a reduced susceptibility toCOVID-19, although this does not imply definitive protective. Noteworthy associations were identified betweenABO blood groups and specific COVID-19 symptoms, including headache, chronic underlying conditions,chest discomfort, and sore throat. The hospitalization among patients with blood group AB was higher thanthat observed in other blood groups (10.8%), while it was notably lower in patients with blood group O (4.6%,P=0.038).Conclusion: Our findings suggest a significant association between ABO blood groups, H. pylori infection, andsusceptibility to COVID-19. These factors may contribute to disease severity and warrant further investigationfor potential clinical implications.